Intercalation of Lithium inside Bilayer Buckled Borophene: A First Principles Prospective. Issue 7 (15th July 2021) - Khan, Muhammad Isa; Aslam, Sheeza; Majid, Abdul; Gillani, Syed Sajid Ali
Abstract : It is keen wish of scientists to develop anode materials having low volume expansion and large capacity with high mobility. Therefore, lithium (Li) has been intercalated in bilayer buckled borophene to improved the adsorption energy, theoretical capacity, open circuit voltage (OCV), diffusion barrier, and structural stability. Here, we investigated the bilayer b-borophene as anode material for Li-ion batteries using first principle calculations. The intercalation of Li preserved the metallic nature of borophene and no volume expansion was found for a fully lithiated structure. This theoretical capacity of 1859 mAh/g, diffusion barrier 80 eV, and OCV 0.08 V indicate that intercalation improves said parameters compared to commercially used Graphene and prove it as a potential candidate for anode material in Li-ion batteries.